INDUSTRIAL RELATIONS DISPUTE CLAIMS TERMINATION BY WORKERS (Case Study of Case Number 972K/Pdt.Sus-PHI/2018) - Sukma Permana, Yana; Saepudin, Aep (CV. Era Digital Nusantara, 2022)
Indonesia is a state of law, as stated in Article 1 paragraph (3) of the 1945 Constitution, which reads